ANALISIS NARASI VISUAL PADA IKLAN LAYANAN MASYARAKAT STEREOTIPE-Z - Iwan Muhammad Ridwan (Wacadesain, 2021)
Generation-Z is synonymous with individualistic culture, loves to watch, tends not to like reading, instant generation where anything can be achieved by search engines via the internet. This has led to Generation-Z's indifference to their environment and their future fate which will face a demographic bonus. This ignorant and individualistic attitude has earned them the nickname of a generation that looks down and has no room for comment. Through the awareness of a Public Service Announcement entitled Stereotype-Z, this Generation-Z image was tried to be awakened. Using a phenomenological approach and Charles Sander Peirce's semiotic methods, this Stereotype-Z public service advertisement reveals the various problems faced by Generation-Z and its challenges in the future. So that the alternative offered is awareness that must be built through individuals who have influence in fellow Generation-Z circles